A tertiary center experience with velopharyngeal surgical techniques for treatment of snoring and obstructive sleep apnea. Issue 3 (June 2018) - Karakoc, Omer; Binar, Murat; Aydin, Umit; Genc, Hakan; Akcam, Timur; Gerek, Mustafa
Abstract: Objectives: The aim of this study was to assess the outcomes of patients who treated with the relatively new surgical procedures; anterior palatoplasty (AP), Cahali lateral pharyngoplasty (CLP), and expansion sphincter pharyngoplasty (ESP) for habitual snoring or obstructive sleep apnea (OSA). Methods: Prospective series of 93 patients were evaluated. The performed surgical techniques, polysomnographic outcomes, pre- and postoperative clinical parameters, and complication rates were assessed. Results: There were 14 snorers and 79 OSA patients. The mean age was 40.7 years, mean BMI was 27.67 kg/m 2, and the mean follow-up time was 5.90 months. There were 30 subjects in AP, 30 subjects in CLP, and 33 subjects in ESP groups. Apnea hypopnea index (AHI) improved from 16.90 to 14.27 (p = 0.135) in AP, from 17.69 to 12.05 in CLP (p = 0.004), and from 26.83 to 9.08 in ESP groups (p < 0.001). When surgical success criteria is defined as more than 50% reduction in AHI to final AHI <15 events/h, success rates were 45%, 64%, and 74% in AP, CLP, and ESP groups, respectively. Epworth Sleepiness Scale and visual analog scale for snoring significantly decreased after all procedures (p < 0.05). The minimum oxygen saturation significantly increased after all procedures, however, only ESP caused statistically significant improvements in oxygen desaturation index, mean SaO2 and the percentage of sleep time with SaO2 below 90%. During the follow-up period, 61 of 93 patients (65.6%) indicated one or more complaints, but none of them was persistent. Conclusion: We suggest that these relatively new velopharyngeal surgical techniques are effective in the management of snoring and OSA without causing persistent side-effects, and ESP is one step ahead of the other two techniques.